2023
DOI: 10.1007/s00425-023-04277-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression profile of the SMAX/SMXL family genes in chickpea and lentil provide important players of biotechnological interest involved in plant branching

Marcos Fernando Basso,
Felice Contaldi,
Fabrizio Lo Celso
et al.

Abstract: Main conclusion SMAX/SMXL family genes were successfully identified and characterized in the chickpea and lentil and gene expression data revealed several genes associated with the modulation of plant branching and powerful targets for use in transgenesis and genome editing. Abstract Strigolactones (SL) play essential roles in plant growth, rooting, development, and branching, and are associated with plant resilience to abiotic and biotic stress co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 86 publications
0
33
0
Order By: Relevance
“…In Arabidopsis , overexpression of AtD27 -like1 in the d27 mutant effectively reinstated the phenotype of increased branching, thereby confirming the involvement of D27 in the biosynthesis of SL [ 58 ]. In a chickpea and lentil study, the majority of SMAX and partner genes were found to exhibit a positive association with the branching level of plants [ 59 ]. In this study, the expression of D27 was twofold lower in the DUs than in the SUs.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , overexpression of AtD27 -like1 in the d27 mutant effectively reinstated the phenotype of increased branching, thereby confirming the involvement of D27 in the biosynthesis of SL [ 58 ]. In a chickpea and lentil study, the majority of SMAX and partner genes were found to exhibit a positive association with the branching level of plants [ 59 ]. In this study, the expression of D27 was twofold lower in the DUs than in the SUs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two contrasting cultivars of chickpea and lentil were selected dealing with plant branching, according to a previous study carried out by Basso et al (2024a). The chickpea cultivars Blanco lechoso and FLIP07-318C were used as little and highly branched, respectively.…”
Section: Plant Materialsmentioning
confidence: 99%
“…For this study, the chickpea cultivars Blanco lechoso (little branched) and FLIP07-318C (highly branched), and lentil cultivars Castellana (little branched) and Campisi (highly branched) were selected based on a previous study where the architecture/branching of these four cultivars was characterized and, among several cultivars, these four were considered most contrasting for this phenotype (Basso et al, 2024a). The cultivars Blanco lechoso and Castellana are characterized by presenting a low number of lateral branches and a dominant, well-defined, and semierect stem (Scarrone-type plant architecture; Halléand Oldeman, 1970).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations